Historical perspective: The pros and cons of conventional outcome measures in Parkinson's disease - Lim, Shen Yang; Tan, Ai Huey (Elsevier, 2018)
Background Conventional outcome measures (COMs) in Parkinson's disease (PD) refer to rating scales, questionnaires, patient diaries and clinically-based tests that do not require specialized equipment. Methods It is timely at this juncture - as clinicians and researchers begin to grapple with the “invasion” of digital technologies - to review the strengths and weaknesses of these outcome measures. Results This paper discusses advances (including an enhanced understanding of PD itself, and the development of clinimetrics as a field) that have led to improvements in the COMs used in PD; their strengths and limitations; and factors to consider when selecting and using a measuring instrument. Conclusions It is envisaged that in the future, a combination of COMs and technology-based objective measures will be utilized, with different methods having their own strengths and weaknesses. Judgement is required on the part of the clinician and researcher in terms of which instrument(s) are appropriate to use, depending on the particular clinical or research setting or question.